Development and characterisation of self-assembled graphene hydrogel-based anodes for bioelectrochemical systems - Lescano, Mariela Ines (2018)
In this work, we report a simple and scalable method to produce high efficiency 3D graphene-based electrodes (GH) for bioelectrochemical systems. GH were obtained by self-assembly of graphene oxide, through slow reduction with ascorbic acid over conductive mesh-works (carbon cloth and stainless-steel). The GH structure and composition were characterised by electron microscopy (SEM) and spectroscopy (FTIR and Raman), whereas the electrodes' performance was tested by chronoamperometry and cyclic voltammetry in a microbial electrolysis cell (MEC) inoculated with a pure culture of G. sulfurreducens. The hydrogel had a broad pore size distribution (>1 μm), which allowed bacterial colonisation within the framework. The macro-porous structure and chemical properties of the hydrogel rendered a higher bacterial loading capacity and substrate oxidation rate than other carbonaceous materials, including different reported graphene electrodes, which significantly increased MEC performance.